2018
DOI: 10.1007/s10791-018-9333-2
|View full text |Cite
|
Sign up to set email alerts
|

A topic recommender for journalists

Abstract: The way in which people acquire information on events and form their own opinion on them has changed dramatically with the advent of social media. For many readers, the news gathered from online sources become an opportunity to share points of view and information within micro-blogging platforms such as Twitter, mainly aimed at satisfying their communication needs. Furthermore, the need to deepen the aspects related to news stimulates a demand for additional information which is often met through online encycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Therefore, future work should aim to find more robust ways to incorporate the temporal aspect in the ranking function [22]. A possible way to achieve that is to identify temporal phenomena such as trending terms or entities in the underlying news article collection [22] or in external sources such as social media [8]. Furthermore, we have found that this task is more challenging when the query event involves entities that appear more frequently in the collection, which we plan to further study in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future work should aim to find more robust ways to incorporate the temporal aspect in the ranking function [22]. A possible way to achieve that is to identify temporal phenomena such as trending terms or entities in the underlying news article collection [22] or in external sources such as social media [8]. Furthermore, we have found that this task is more challenging when the query event involves entities that appear more frequently in the collection, which we plan to further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on developing automatic applications to support writers has focused on designing tools that track and filter information from social media to support journalists [11,53]. Cucchiarelli et al [8] track the Twitter stream and Wikipedia edits to suggest potentially interesting topics that relate to a new event that a writer can include in their narrative when reporting on the event. In contrast, instead of relying on external sources, we aim to retrieve news articles that describe events from the past that can help the writer expand the incomplete narrative about a specific event.…”
Section: Related Work 81 Supporting Narrative Creationmentioning
confidence: 99%
“…There are contexts in which one may want to serendipitously recommend new items that the user probably will like but may not be aware of based on associated interests and external events [ 16 , 50 ]. With limited exceptions [ 6 , 88 ], there has been sparse research in the serendipity area with large-scale datasets.…”
Section: Prior Workmentioning
confidence: 99%
“…In their methodology component metrics are combined, and journalists are proposed with topics in breaking news situations in which there is an information need (detected from online news, Twitter and Wikipedia), but not relevant supply for aspects not covered by the news media. [15][16][17][18] Considering the methodology, we find the work by Diakopolos et al interesting in the sense that they used a design process to produce a use case of a useful prediction tool to spot eyewitness information from social media, arranging interviews with reporters to understand their use of social media and journalistic information needs before developing the tool [22].…”
Section: Related Workmentioning
confidence: 99%